Thermalization and ionization of metal atoms of operating environment at a metal ion-sputtering source - Baturin, V.A.; Litvinov, P.A.; Pustovoitov, S.A.; Roenko, O.Yu. (Вопросы атомной науки и техники, 2021)
Fast atoms sputtered on a hot metal surface were suggested for thermalization at a metal ion-sputtering source and for further desorption into a discharge with temperature, which is equal to the temperature of the surface. In the suggested construction of the source, atom thermalization process is realized on an interior surface of an anode of the Penning discharge cell in an oscillation area of ionizing electrons. It has been experimentally shown that the proposed method of thermalization of Fe atoms increases the fraction of Fe⁺ ions in the extracted ion beam by three times. У джерелі металевих іонів розпилювального типу запропоновано проводити процес термалізації швидких розпорошених атомів на гарячій металевій поверхні з наступною їх десорбцією в розряд з температурою, що дорівнює температурі цієї поверхні. У розглянутій конструкції джерела термалізація атомів реалізована на внутрішній поверхні анода пенінговської розрядної комірки в області осциляції іонізуючих електронів. Експериментально показано, що термалізовані таким чином розпорошені в розрядній камері атоми Fe збільшують фракцію Fe⁺ в екстрагованому іонному пучку в три рази. В источнике металлических ионов распылительного типа предложено производить процесс термализации быстрых распыленных атомов на горячей металлической поверхности с последующей их десорбцией в разряд с температурой, равной температуре этой поверхности. В рассматриваемой конструкции источника термализация атомов реализована на внутренней поверхности анода пеннинговской разрядной ячейки в области осцилляции ионизирующих электронов. Экспериментально показано, что термализованные таким образом распыленные в разрядной камере атомы Fe увеличивают фракцию Fe⁺ в экстрагируемом ионном пучке в три раза.